Status Hukum Majelis Kehormatan Notaris Dalam Prespektif Tata Usaha Negara - Surya Hartarto Purwowibowo (Faculty of Law, University of Jember, Indonesia, 2021)
A notary of social institutions are in indonesia, of the needs arising from desires evidence any law keperdataan among mereka.akta authentic can result in dispute, so we needed evidence any written in the form of photocopies minuta and testimony a notary certificate. A notary can be checked as the officials who makes a covenant. Investigators, the public prosecutor and the judge called a notary and received a photocopy of certificate minuta. The legal status of the notary is as the manager of a mandate from the minister of justice and human rights in giving approval or rejection to be examined by a notary, investigators prosecutors and judges in the judiciary and the copy of deed minuta used as evidence a related reports of one party. The legal status is a situation when a party considered eligible to apply for dispute resolution. The decision made the honor notary can be sued by a notary in judicial administrative as there are two decisions that court decisions administrative number 21/G/2017/PTUN.SBY and 24/G/2017/PTUN.SBY. An authentic deed load in accordance with the will of the parties. Formal to make clear the notarial deed and earnest perceptible by the parties with read it. Notaries should not leave due examination are responsible for a notary is an expression of truth when. certificateThe need for inspection by the notary of a notary can be sued in state administrative courts cause kekabuaran meaning administrative officials.